2015
DOI: 10.18632/oncotarget.6667
|View full text |Cite
|
Sign up to set email alerts
|

In silico pathway analysis in cervical carcinoma reveals potential new targets for treatment

Abstract: An in silico pathway analysis was performed in order to improve current knowledge on the molecular drivers of cervical cancer and detect potential targets for treatment. Three publicly available Affymetrix gene expression data-sets (GSE5787, GSE7803, GSE9750) were retrieved, vouching for a total of 9 cervical cancer cell lines (CCCLs), 39 normal cervical samples, 7 CIN3 samples and 111 cervical cancer samples (CCSs). Predication analysis of microarrays was performed in the Affymetrix sets to identify cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…From these probesets, six genes ( AURKA , DTL , HMGB3 , KIF2C , NEK2 , and RFC4 ) were overexpressed in CC cell lines compared to cancer samples, suggesting their potential role as biomarkers in CC early diagnosis. 53 One of these genes, such as RFC4 , was also identified in our study. Furthermore, our conclusion generated from both expression and survival analysis suggested that RFC4 might have a prognostic value.…”
Section: Discussionsupporting
confidence: 70%
“…From these probesets, six genes ( AURKA , DTL , HMGB3 , KIF2C , NEK2 , and RFC4 ) were overexpressed in CC cell lines compared to cancer samples, suggesting their potential role as biomarkers in CC early diagnosis. 53 One of these genes, such as RFC4 , was also identified in our study. Furthermore, our conclusion generated from both expression and survival analysis suggested that RFC4 might have a prognostic value.…”
Section: Discussionsupporting
confidence: 70%
“…Through direct stimulation, cell cycle genes synergize with E6/E7 oncoprotein-mediated blockade of cell cycle suppressors, p53 and RB, to promote cancer progression [ 40 ]. More recently, an in silico pathway analysis revealed that deregulation of the cell cycle is one of the major trademarks in cervical cancer [ 41 ]. In addition, this study also suggests that the major components of cell cycle pathway, such as CDK1/2, could be potential new targets for treating cervical cancer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an in silico pathway analysis revealed that deregulation of the cell cycle is one of the major trademarks in cervical cancer [ 41 ]. In addition, this study also suggests that the major components of cell cycle pathway, such as CDK1/2, could be potential new targets for treating cervical cancer [ 41 ]. However, this concept has not yet been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, sodium butyrate has been shown to influence the adhesion and growth-regulating galectin network that controls the proliferation of human colon cancer cells in vitro (10). DNA microarray analysis has contributed to our knowledge of tumour biomarkers and their potential suitability as targets of anticancer therapy as revealed by bioinformatics analyses (11)(12)(13).…”
mentioning
confidence: 99%